How Hospitals Overcame Disruptions in the Early Stages of the COVID-19 Pandemic: A Case Study from Tokyo, Japan - Ayako Honda; Toyomitsu Tamura; Hiroko Baba; Haruka Kodoi; Shinichiro Noda (Taylor & Francis Group, 2023)
ABSTRACTThe COVID-19 pandemic has caused serious disruptions to health systems across the world. While the pandemic has not ended, it is important to better understand the resilience of health systems by looking at the response to COVID-19 by hospitals and hospital staff. Part of a multi-country study, this study looks at the first and second waves of the pandemic in Japan and examines disruptions experienced by hospitals because of COVID-19 and the processes through which they overcame those disruptions. A holistic multiple case study design was employed, and two public hospitals were selected for the study. A total of 57 interviews were undertaken with purposively selected participants. A thematic approach was used in the analysis. The study found that in the early stages of the pandemic, faced with a previously unknown infectious disease, to facilitate the delivery of care to COVID-19 patients while also providing limited non-COVID-19 health care services, the case study hospitals undertook absorptive, adaptive, and transformative actions in the areas of hospital governance, human resources, nosocomial infection control, space and infrastructure management, and management of supplies. The process of overcoming the disruptions caused by the pandemic was complex, and the solution to one issue often caused other problems. To inform preparations for future health shocks and promote resilience, it is imperative to further investigate both organizational and broader health system factors that build absorptive, adaptive, and transformative capacity in hospitals.